PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN BERDASARKAN MASALAH PADA MATERI BILANGAN PECAHAN UNTUK SISWA KELAS VII SMP/MTs - Sari Bangun Putri Dewi; Armis '; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to develop mathematics learning device with problem based learning’s model of fraction number for 7th grade SMP/MTs. Learning device in this study are lesson plans and activity student sheet. Lesson plans and activity student sheet are developed to structured in accordance with the steps of the scientific approach that is observing, questioning, reasoning, trying, and communicating. This study method used is 4D model that consist of define, design, development, and disseminat. Because of time and cost, the study was only to development step. Based on the data analysis of mathematics learning devices is very valid with mean validity of lesson plans is 3,85, and mean validity of student activity sheet is 3,73. This student activity sheet has also reached the practical qualification with mean percentage of student responses is 100% on a small test group. Based on the results of this study can be concluded that the product of lesson plans and activity student sheet the mathematic based on the curriculum of 2013 on the fractional material to SMP/MTs with the use of the problem based learning’s model is very valid and practice.Keywords: Fraction Number, Mathematics Learning Device, Problem Based Learning, Research and Development.